Dentoalveolar, periodontal and skeletal effects of maxillary expansion techniques assisted by temporary anchorage devices compared with conventional protocols in growing patients with transverse maxillary deficiency: A systematic review and metaanalysis (2024)
ABSTRACT: Objectives: To synthesize the dentoalveolar, periodontal and skeletal changes that occur when using maxillary expansion techniques assisted by temporary anchorage devices compared to conventional protocols. Methods: Five databases and gray literature were consulted, up to December 2023, focusing on intervention designs and excluding other types of studies. The quality assessment was conducted by using the adaptation for orthodontics of the CONSORT statement, the guidelines for reporting non randomized studies, the RoB-2 tool, and the ROBINS-I tool. A descriptive summary and meta analysis using RevMan 5.4 were performed. Results: Nine clinical trials were included (n = 377 patients, mean age 13.2 0.6) with a diagnosis of transverse maxillary deficiency. The analyzed studies showed qualitative dentoalveolar and periodontal changes after expansion, which were greater on the maxillary first premolars in tooth-borne appliances. Meta-analyses for some effects were included from two studies (n = 64); patients who used tooth-borne appliances had greater effects of buccal intracoronal width between the premolars with statistically significant differences (Std Mean difference 2.34; 95% CI: 0.04–4.65 p = 0.05). Conversely, those patients who used bone-borne or hybrid appliances had greater effects of buccal intracoronal width between molars with statistically significant differences (Std Mean difference 0.64; 95% CI: 1.38–0.10; p = 0.09). Conclusions: According to the studies analyzed, all measurements increased in the intervention groups after expansion. Quantitative analyses show different findings at dentoalveolar level when tooth-borne, bone-borne or hybrid appliances are considered. Nevertheless, the results should be taken with caution due to the heterogeneity of the studies. The protocol was registered at PROSPERO (CRD42021283170), with no funding to report.